GE_GERICHTE P/6956/2023 vom 27. Juli 2023 - GE Cour de justice (2023)
DÉCISION D'IRRECEVABILITÉ;COMPÉTENCE RATIONE LOCI;INFRACTIONS CONTRE LE PATRIMOINE;ASTUCE | CPP.310; CP.3; CP.8; CP.138; CP.146; CP.158